Photodarkening and photobleaching impact on 1030 nm fiber laser emission. (2nd February 2015) - Gebavi, Hrvoje; Robin, Thierry; Mechin, David; Ferrari, Maurizio; Taccheo, Stefano
Abstract: In this paper, photodarkening (PD) and photobleaching (PB) impact on 1030 nm ytterbium doped fiber laser emission are presented. In comparison with 1070 nm fiber laser built from the same kind of aluminosilicate fiber, the 1030 nm fiber laser shows less PD loss as the consequence of lower inversion and the possibility of almost complete efficiency recovery obtained by 633 nm PB. The results indicate the importance of inversion in PD process rather than photons interplay with the phenomenon as well as the occurrences of lower energy de-activation defects.